Aspiracje nauczycieli szkół rolniczych w zakresie kształcenia ich dzieci - Bartosiak-Tomusiak, Mariola (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 1998)
The problems of professional aspiration examined in the paper are the subject of three studies: psychology, pedagogics and sociology. Results of an investigation presented in this paper give cause for optimism. The present economic and political changes in Poland favour aspiration for higher level of teaching.